Pendidikan Anak Dalam Islam (Studi Tentang Epistemologi Pendidikan Abdullah Nasih Ulwan) - Ahmad Sukri Harahap (Hikmah, 2015)
Epitemologi as part of a philosophy invites seek truth in terms of the source, the origin of knowledge was obtained. The study of epistemology is synergized with science education, make the scientists examine the source of knowledge in the eyes of science education. Abdullah Nashih Ulwan tell epistemology of education within the framework of educating children as a trust from God the Creator, the source of thought are of the Koran and Hadith. He said parents should provide early education with a full sense of responsibility because it is a mandate from God Almighty. If parents really perform well, then tuuan achieved the happiness and ketenanangan life will be achieved.